IMMU-33. CCL4 DRIVES GLIOBLASTOMA (GBM) TUMOR MICROENVIRONMENT (TME) REPROGRAMMING AFTER TREATMENT WITH A NOVEL MRNA VACCINE. (14th November 2022) - Dastmalchi, Farhad; Thomas, Nagheme; Frain, Matt; Ebrahim, Ghaidaa; Moore, Ginger; Tomdio, Macaulay; Mendez-Gomez, Hector; Sayour, Elias; Subramaniam, Vignesh; Angelini, Thomas; Mitchell, Duane; Rahman, Maryam
Abstract: INTRODUCTION: Our group has developed a patented vaccine platform that combines an mRNA-nanoparticle with CXCL9 loaded polyethylene glycol (PEG) hydrogel. The HCM vaccine is given SQ and recruits a diverse immune cell population to deliver a large payload of mRNA. The objective of these studies was to evaluate the effects of HCM vaccination on the TME. METHODS: C57BL/6 mice underwent intracranial implantation of KR158 or GL261 glioma cells. The HCM vaccine was formulated with total tumor mRNA, DOTAP, CXCL9 and PEG hydrogel created in collaboration with the College of Engineering. Survival studies were analyzed with the Mantel-Cox test. Flow cytometry and ELISA data was analyzed using ANOVA. Graphpad was used for statistical analysis. RESULTS: Intracranial tumor bearing mice were treated with SQ or intracranial injection of the HCM vaccine (total tumor mRNA, DOTAP, CXCL9, PEG hydrogel). SQ HCM delivery resulted in significant survival benefit whereas intracranial delivery did not (p = 0.0012). In a separate experiment, tumors and spleens were collected for flow cytometry. A significant increase in antigen specific CD8 T cells was found. Separately, after SQ vaccination, tumors were collected for PCR analysis. Tumors treated with HCM vaccination demonstrated significant upregulation of CCL4 and CXCR6. Intracranial tumor bearing mice were treated with HCM vaccination with or without blockade of CCL4. CCL4 blockade resulted in no survival benefit of the vaccine. CONCLUSION: The HCM vaccine results in migration of antigen specific CD8 T cells within the TME and significant increases in CCL4. HCM vaccine efficacy is dependent on CCL4.